Halofuginone- and Chitosan-Coated Amnion Membranes Demonstrate Improved Abdominal Adhesion Prevention - Scott Washburn; Jamie L. Jennell; Steve J. Hodges (The Scientific World Journal)
Our objective was to determine whether coating the amniotic membrane with halofuginone, a type 1 collagen synthase inhibitor, with or without the hemostasis-inducing substance chitosan, reduced the number and severity of adhesions in the rat uterine horn injury model. Sixty retired breeder Sprague-Dawley rats underwent midline laparotomy and a zone of ischemia was created in the left uterine horn of each animal. Rats were randomized to one of six treatment groups: (1) untreated control, (2) oxidized regenerated cellulose (Interceed®) (ORC), (3) plain amnion, (4) amnion coated on both sides with 0.5% solution of halofuginone (HAH), (5) amnion coated on one side with 0.5% halofuginone and on the other side with chitosan (CAH), or (6) amnion coated on both sides with chitosan (CAC). The zone of ischemia in each left uterine horn was wrapped in each treatment. Rats were sacrificed 2 weeks after laparotomy, and adhesions were counted and scored for severity. Data were analyzed using Chi square and a p <0.05 was considered significant. Our results showed that there were no differences in the percentage of animals with adhesions in the untreated, ORC, plain amnion, or CAC groups. No adhesions formed in any animal in the HAH group and only 14% of the animals developed adhesions to the uterine horn in the CAH group (p < 0.05). The percentage of animals with moderate and severe adhesions did not differ between untreated controls and the ORC groups, but were significantly reduced in all four of the amnion groups: plain amnion, HAH, CAH, and CAC (p < 0.05). Amnion coated with halofuginone alone or in combination with chitosan reduced the percentage of animals with adhesions, as well as the percentage of animals with moderate and severe adhesions compared to untreated controls and the ORC group in the rat uterine horn injury model. Amnion alone or coated with chitosan reduced the percentage of rats with moderate and severe adhesions, but not the percentage of rats with adhesions of any type compared to both untreated controls and the ORC group in the rat uterine horn injury model.